Tampilan Feed Instagram sebagai Mediasi antara Social Media Marketing dan Purchase Intention - Anannda Lailatul Fauziah; Ratih Amelia (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2026)
Digital marketing via Instagram indicates that high levels of Social Media Marketing activity do not always lead to an increase in Purchase Intention. This suggests the influence of other factors, particularly visual aspects reflected in the Instagram feed as a representation of the brand. This study aims to analyze the influence of Social Media Marketing on Purchase Intention and to test the role of the Instagram feed as a mediating variable in this relationship. A quantitative approach was employed using a survey method involving 110 respondents who are Instagram users and follow the Kopi Kenangan account. Data were collected via a questionnaire and analyzed using the PLS-SEM method. The results indicate that Social Media Marketing has a positive and significant influence on Purchase Intention as well as on the Instagram feed’s visual presentation. The Instagram feed appearance also has a significant effect on Purchase Intention and acts as a mediating variable in the research model. These findings confirm that the Instagram feed appearance functions not only as an aesthetic element but also as a visual mechanism that reinforces the influence of marketing activities on consumer responses. This study contributes by positioning feed management as part of a visual marketing strategy within the framework of Social Media Marketing. Keywords: Social Media Marketing; Instagram Feed Appearance; Purchase Intention; Visual Marketing; Mediation